An Analysis of Idiomatic Expression In Voice Lines Heroes in Dota 2 Video Game - Ramandhika Aditya Wikarta; Arjulayana Arjulayana; Nargis Nargis; Noor Azlan Ahmad Zanzali (Globish: An English-Indonesian Journal for English, Education, and Culture, 2025)
This research analyzes idiomatic expressions in the voice lines of heroes in the video game Dota 2, using Charles Hockett's theory. This research highlights the potential of video games as an effective tool for language learning, offering native English speakers an authentic context to understand and internalize idiomatic expressions. Through qualitative analysis, 50 idiomatic expressions were identified and classified into six categories: Substitutes, Proper Names, Abbreviations, English Phrase Compounds, Allusions, and Slang. Specifically, Substitutes accounted for 8 idioms, Proper Names for 12 idioms, English Phrasal Compounds for 7 idioms, Figures of Speech for 14 idioms, and Slang for 9 idioms, with no examples of Abbreviations. Each idiom's contextual meaning is analyzed, thus contributing to a deeper understanding of their function in the game. The insights gained create an equivalence between digital games and language education, providing valuable implications for gamers and educators or learners in utilising video games for language development.